ASSESSMENT OF COGNITIVE STATUS IN CEREBRAL DISORDERS IN PATIENTS WITH DIABETES MELLITUS - Otabek B. Nadjmitdinov ,; Akramjon A. Sobirov ,; Ilxomjon A. Jalolov , (Central Asian Journal of Medicine, 2025)
Diabetes mellitus is one of the most significant risk factors for the development of cerebrovascular disorders, which can lead to a decrease in cognitive functions. This study examines the relationship between diabetes mellitus and cognitive impairment due to cerebral changes.